Neuroradiologic Correlates of Cognitive Impairment in Adult Moyamoya Disease - Mogensen, M.A.; Karzmark, P.; Zeifert, P.D.; Rosenberg, J.; Marks, M.; Steinberg, G.K.; Dorfman, L.J. (American Journal of Neuroradiology, 2012)
BACKGROUND AND PURPOSE: MMD has been shown to result in impairment of executive functioning in adults. The purpose of this study was to correlate presurgical neuropsychological assessments with the severity of primary MMD as measured by CBF and CVR and with secondary damage from MMD as estimated by cortical stroke and WMD. MATERIALS AND METHODS: A retrospective analysis of 31 adult patients with MMD was performed. Xe-CT was used to obtain CBF and CVR, and MRI was reviewed to grade cortical stroke and WMD. Two tests of executive functioning (FAS and TMT-B) were correlated with imaging findings. A multiple regression analysis was performed. RESULTS: There was a significant overall positive relationship between mean CBF and FAS (P = .038) and TMT-B scores (P = .014). A significant negative relationship was present between the WMD score and the FAS (P = .009) and TMT-B scores (P = .015). Per-region analysis demonstrated that FAS and TMT-B scores were significantly decreased by the presence of a posterior stroke (P < .0001 and P = .001) or WMD (P = .006 and P = .004). All patients with posterior parieto-occipital WMD or stroke also had secondary disease in the anterior regions. CONCLUSIONS: Impaired executive functioning in adults with MMD is most strongly associated secondary damage in the form of WMD or cortical stroke. The effect is most profound with parieto-occipital lobe involvement, likely a reflection of overall disease severity. Increasing global WMD burden may be a better indicator of cognitive decline than cortical infarction. Patients with higher baseline CBF seem to have better cognitive functioning. CVRcerebral vascular reserveFASControlled Oral Word-Association TestMMDMoyamoya diseaseTMT-BTrail Making Test, Part BWMDwhite matter diseaseXe-CT133xenon-enhanced CT